Can Moroccan Law Ensure Substantive Justice in Protecting Private Life from AI’s Impact? - Ezzerouali, Souad; Arifin, Ridwan; Banane, Mohamed Cheick (Susbtantive Justice International Journal of Law, 2025)
This study examines the impact of the digital revolution and artificial intelligence (AI) on personal privacy in Morocco, within the framework of the country’s national digital strategy. As AI technology rapidly evolves, it raises significant concerns about the privacy of individuals, particularly with the unauthorized use or disclosure of personal data through algorithms. These challenges extend to various sectors, including economics, where e-commerce thrives, and politics, where AI can influence election campaigns. The research contributes to understanding how Moroccan law addresses privacy protection in the digital age. It critically reviews key legal instruments such as the Civil Code, the Consumer Protection Law, the Personal Data Protection Law, and the Product Safety Law, assessing their adequacy in safeguarding individuals’ rights. The study highlights the gaps in existing legislation, emphasizing the need for stronger legal frameworks to protect privacy in the face of advancing AI technologies. Key objectives of the study include assessing AI's effects on private life, evaluating the effectiveness of Moroccan laws in protecting privacy, and exploring the roles of the state and civil society in promoting legal and technical awareness. Using a descriptive-analytical approach, the research analyzes privacy protection laws in light of AI’s development. The study concludes with several recommendations: raising awareness about AI risks, enhancing existing privacy laws, and creating a comprehensive legal and technical framework that ensures stronger digital security for Moroccan citizens. These contributions aim to guide the protection of privacy and substantive justice in the era of artificial intelligence.